No Judge Required: M (By Her Litigation Friend, MRS B) v A Hospital; M (Withdrawal of Treatment: Need For Proceedings) (2017) EWCOP 19. (29th January 2018) - Pywell, Stephanie M
Abstract: The two titles of the judgment on which this commentary is based reflect the fact that its scope was wider than resolving the legal matter at issue between two parties. It records the reasons for Jackson J's decision on a set of facts, it clarifies whether legal proceedings were necessary and the form that they should take, and it explains why the Court of Protection appointed a patient's mother as her litigation friend. The case arose from a request for a declaration that it would be lawful to withdraw clinically assisted nutrition and hydration from a woman with Huntingdon's disease who had been in a minimally conscious state for about one year. The application for withdrawal was supported by everyone whose evidence was heard. Jackson J stated that, in such cases, clinicians would be protected by the Mental Capacity Act 2005, and that court proceedings were therefore unnecessary. He explained that, provided that certain criteria are met, and the circumstances are appropriate, a court may appoint a family member or friend—rather than the Official Solicitor—to act as a litigation friend. This commentary explores the implications of this judgment in the context of very recent clinical developments.